Roadmap for livestock monitoring, reporting, and verification improvement in Ethiopia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
This workshop is part of the Australian Centre for International Agricultural Research (ACIAR) supported CCAFS project “Enhancing capacities for measurement, reporting and verification (MRV) of sustainable livestock actions in Ethiopia.” Ethiopia’s Nationally Determined Contribution (NDC) states the intention to reduce greenhouse gas (GHG) emissions from the livestock sub-sector. The national GHG inventory is one of the main tools through which Ethiopia can measure and report livestock subsector GHG emissions.